School Transition to the State-Social Management System Based on the Project Approach Application - N. V. Nemova (Russian State Vocational Pedagogical University, 2015)
The paper looks at the opportunities for the school transition to the state-social management system based on the project approach application. The principle methods and procedures for the project initiation are observed along with the project organization and planning, recourse provision and project monitoring. According to the author, the most effective form of initiating the management modernization project simultaneously involves the two participants: the internal (school management) and external (educational management organizations), provided that the external one sets the main requirements. Using the project approach allows the fast knowledge accumulation for further application. In this regard, it is more efficient than the program-targeted management requiring more time and effort for fulfilling the program. In author's opinion, the project method can be extended to solving the problem situations. For example, its appli- cation is the most expedient in step-by-step implementation of the state-social management, given that not every school can restructure the existing management system by itself.